Selection of software, a systematic review - Rojas Duarte, Andrés Leonardo; Pinzón, Yoan; Cortez Aldana, Feliz Antonio (UNIVERSIDAD ANTONIO NARIÑO, 2015)
Software selection is a process in which several decision makers are involved, which have different preferencesthat could be mutually exclusive,this added to the different criteria that should be consider when evaluating the alternatives, makes this type of situation a multicriteria decision problem, that can be approached from the multiple-criteria analysis perspective. In this paper, a systematic review of software selection is presented, with the main goal of establishing an academic support for this type of process. To elaborate the state of the art, research questions, the inclusion criteria of the documents, the search process and analyze data to answer the questions identified, were defined. The main contribution of this paper is the determination of the methodologies used and the set of criteria that can be taken as a basis for the evaluation of alternatives, to choose the most appropriate according to the context of the software selection process.